2003
DOI: 10.1136/ip.9.3.261
|View full text |Cite
|
Sign up to set email alerts
|

Home delivery of an injury prevention kit for children in four French cities: a controlled randomized trial

Abstract: Objectives:Home delivery of counselling and safety devices to prevent child injuries could help parents to adopt safe behaviour. The aim of this study was to test a safety kit designed and used in Quebec (Canada).Design and subjects:One hundred families from four towns in the Paris suburbs were visited at home by nurses or doctors when their child reached 6–9 months. Selection criteria were: primipara, medical problem, psychological, and/or socioeconomic difficulties.Interventions:During the first visit, 50 fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
2
8

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 18 publications
(15 reference statements)
1
48
2
8
Order By: Relevance
“…Estudos da última década identificam potenciais em ações de prevenção 69 , mesmo que haja poucas evidênci-as de redução de injúrias através da utilização de meios como campanhas e doação de equipamentos de proteção [70][71][72][73] . As abordagens que reforçam a necessidade do papel ativo dos pais e responsáveis trouxeram resultados modestos na redução de injúrias 74 .…”
Section: Escorpionismounclassified
“…Estudos da última década identificam potenciais em ações de prevenção 69 , mesmo que haja poucas evidênci-as de redução de injúrias através da utilização de meios como campanhas e doação de equipamentos de proteção [70][71][72][73] . As abordagens que reforçam a necessidade do papel ativo dos pais e responsáveis trouxeram resultados modestos na redução de injúrias 74 .…”
Section: Escorpionismounclassified
“…Studies carried out in the last decade indicated potential preventive measures, 69 even if scant evidence exists regarding the reduction of injuries by means of campaigns and donation of protective equipment. [70][71][72][73] The approaches that underscore the necessity of an active role of parents and surrogates reduced injuries moderately.…”
Section: Scorpion Envenomationmentioning
confidence: 99%
“…Further, implementation of home visits to safety training programs may lead an additional counseling chance for minimizing the hazards in the home. In fact, some previous studies indicate that education programs adapted home visit was effective to decrease the rate of home injuries and injury risks (18,19). We implemented home visits in order to not only identify home safety behaviors of the mothers but also to give counseling to them about injury risks in the home, the appropriate safety products and practices.…”
Section: Discussionmentioning
confidence: 99%